The effect of lauric acid as antimicrobial agent in chitosan-based packaging film - Law, Hoi Ling (2007)
To study the effect of To study the effect of Lauric acid as acid as antimicrobial agent in antimicrobial agent in Chitosan Chitosan-based packaging film. packaging film.